"Seroepidemiology of Hydatid Cyst in Chaharmahal va Bakhtiari Province, Iran" - H Yousefi Darani; M Avijgan; K Karimi; K Manouchehri; J Masood (Tehran University of Medical Sciences, 2003)
Abstract Hydatid cyst is the larval stage of the cestode worm Echinococcus granulosus, which causes echinococcosis in human and some other mammalian. Iran is located in endemic zone of this disease and Chaharmahal va Bakhtiari province, due to existence of sheep husbandry jobs, has a potential for high prevalence of the disease, . Therefore, this investigation was carried out to study seroepidemiology of hydatic cyst in human in this area. In this descriptive study, 1000 serum samples from blood donors and 1524 from patients referred to clinical laboratories of the province, were subjected to immunoelectrophoresis to detect seropositive cases for hydatid cyst. The prevalence of hydatid cyst in sample population (2524) were 4.8 percent. The infection rate of the disease among males and females was 4.4% and 5.1% respectively. Lordegan city had the highest rate of the infection while Ardal city had the lowest one. Blood donors had a lower infection rate compared with patients referred to clinical laboratories. The results of this investigation revealed that there was a major difference between the prevalence of hydatid cyst in Chaharmahal va Bakhtiari and that of some other parts of the world.